Greenhouse Gas Emission from Solid Waste Disposal Sites in Asia - Ishigaki, Tomonori; Hirata, Osamu; Oda, Takefumi; Wangyao, Komsilp; Chiemchaisri, Chart; Towprayoon, Sirintornthep; Lee, Dong-Hoon; Yamada, Masato (IntechOpen, 2011)
None